A Porous Network of Bismuth Used as the Anode Material for High‐Energy‐Density Potassium‐Ion Batteries. Issue 17 (15th March 2018) - Lei, Kaixiang; Wang, Chenchen; Liu, Luojia; Luo, Yuwen; Mu, Chaonan; Li, Fujun; Chen, Jun
Abstract: Potassium‐ion batteries (KIBs) are plagued by a lack of materials for reversible accommodation of the large‐sized K + ion. Herein we present, the Bi anode in combination with the dimethoxyethane‐(DME) based electrolyte to deliver a remarkable capacity of ca. 400 mAh g −1 and long cycle stability with three distinct two‐phase reactions of Bi↔ KBi2 ↔K3 Bi2 ↔K3 Bi. These are ascribed to the gradually developed three‐dimensional (3D) porous networks of Bi, which realizes fast kinetics and tolerance of its volume change during potassiation and depotassiation. The porosity is linked to the unprecedented movement of the surface Bi atoms interacting with DME molecules, as suggested by DFT calculations. A full KIB of Bi//DME‐based electrolyte//Prussian blue of K0.72 Fe[Fe(CN)6 ] is demonstrated to present large energy density of 108.1 Wh kg −1 with average discharge voltage of 2.8 V and capacity retention of 86.5 % after 350 cycles. Abstract : Bi anodes : In a potassium‐ion battery, bismuth delivers a remarkable capacity of approximately 400 mAh g −1 and cycle stability with three distinct two‐phase reactions of Bi↔KBi2 ↔K3 Bi2 ↔K3 Bi in a dimethoxyethane‐based electrolyte. These properties are ascribed to bismuth′s ability to form 3D porous networks.